2017
DOI: 10.1007/s13201-017-0537-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methyl violet 2B dye from aqueous solution using Nepenthes rafflesiana pitcher and leaves

Abstract: This study reported Nepenthes rafflesiana pitcher (NP) and Nepenthes rafflesiana leaves (NL) as new adsorbents for methyl violet (MV) dye. The experiments were done using 2 h contact time and without any pH alteration (pH 4.4). The effects of pH and ionic strength revealed hydrophobic-hydrophobic interaction as the predominant force of dye interaction with the adsorbent. Both NP-MV and NL-MV followed pseudo-second-order model indicating the adsorption processes may be governed by chemical process. Weber-Morris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The different properties of the palm fronds and developed biochars were characterized by FT-IR, SEM-EDX, XRD, and BET analysis. The adsorption studies of the MnO 2 /PF biochar nanocomposite were investigated in a batch mode at pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), an initial MO concentration of (10-50 mg/L), and an adsorbent dose of (0.01-0.1 g). It was found that the MnO 2 /PF biochar showed the highest micro-mesopores structure and surface area (70.97 m 2 /g), compared to those of other samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different properties of the palm fronds and developed biochars were characterized by FT-IR, SEM-EDX, XRD, and BET analysis. The adsorption studies of the MnO 2 /PF biochar nanocomposite were investigated in a batch mode at pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), an initial MO concentration of (10-50 mg/L), and an adsorbent dose of (0.01-0.1 g). It was found that the MnO 2 /PF biochar showed the highest micro-mesopores structure and surface area (70.97 m 2 /g), compared to those of other samples.…”
Section: Discussionmentioning
confidence: 99%
“…Different materials have been used to ensure the economic feasibility of the wastewater treatment process, such as agricultural waste, since it is abundantly available and renewable [10]. Water lettuce, agrowastes, Nepenthes rafflesiana pitcher, and leaves were also used as potential adsorbents for acid blue 25 (AB25) and methyl violet 2B (MV) dye removal, respectfully [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as observed in Figure 3, the Weber-Morris plot displayed multilinearity behavior. The first linear region indicates the intraparticle diffusion, while the second linear region indicates the slow equilibrium phase [30]. As the intercept of the first linear region of the Weber-Morris plot is not zero, this suggests that intraparticle diffusion is not the rate-controlling step.…”
Section: Kinetics Studiesmentioning
confidence: 99%
“…MV has carcinogenic and mutagenic properties and is also a known irritant that can affect the eyes, skin, and gastrointestinal and respiratory tract [29]. MV also hinders the growth of microorganisms and prevents photosynthesis reactions from taking place in aquatic plants and animals in the environment [30].…”
Section: Introductionmentioning
confidence: 99%
“…Contact time is the time which ensures the duration of agitation time which is sufficient for the adsorption process to reach equilibrium. 26 The rate of adsorption increases with increase in time and becomes constant after attaining equilibrium. This is attributed to the availability of adsorption sites followed by slower adsorption by attaining saturation level after equilibrium.…”
Section: Effect Of Contact Timementioning
confidence: 99%